Research on Synchronous Generators AC Excitation Regulation Control System - Mansi Balram Handi; P. S. Chobe; D. B. Pardeshi (International Journal of Electrical Power and Machine Systems, 2024)
Based on various methods to supply excitation power to the synchronous generator it is categorized in three different types of excitation systems for synchronous motor. The first one is DC excitation system, second is AC excitation system and third one is static excitation system. The increasing size of contemporary power systems ensures system dependability and stability. A better supply of power is vital and has a big influence on improving people's quality of life and economic growth. The AC excitation system is the primary subject of this study. Variable rotor speed is one of the great features of AC excited generator; it enhances power system stability and permits deep operation without step loss. AC excitation generators have independent features for adjusting speed, reactive power, and effective power in addition to variable speed and constant frequency power. Maximum dependability, operating flexibility, and outstanding adjustment performance may be achieved with AC excitation generators by utilizing high-performance variable frequency excitation power sources and suitable excitation control techniques. Synchronous generator functioning depends heavily on the excitation mechanism. The stability of the motor and power system are significantly increased by a well-designed excitation system, which also guarantees the generator's steady and dependable functioning.
Keywords: AC Excitation System; Stability; Synchronous generator; generator; regulation control system